Effect of different surface treatments on polypropylene composites reinforced with yerba mate fibers: Physical, mechanical, chemical, and morphological properties. Issue 45 (6th July 2021) - Borsoi, Cleide; Hansen, Betina; Gemmer, Ruan Ezequiel; Dahlem Júnior, Marcos Aurélio; Francisquetti, Edson Luiz; Zattera, Ademir José; Santana, Ruth Marlene Campomanes; Catto, André Luis
Abstract: This study presents the preparation of post‐consumer polypropylene (r‐PP) composites filled with 30 wt% yerba mate (YM) stick particles. To improve the fiber–matrix adhesion, three surface treatments were performed: alkaline treatment with sodium hydroxide (NaOH) and use of 3‐aminopropyltriethoxysilane (APTS) and maleic anhydride graft polypropylene copolymer (PP‐g‐MA) as coupling agents. Mechanical properties including tensile, flexural, and impact resistance were determined, and chemical (Fourier transform infrared spectroscopy [FTIR]), physical (water absorption), and morphological analyses were performed. The main findings show that the treatments were efficient in improving the mechanical properties of the composites, with emphasis on the r‐PP/YM30/APTS and r‐PP/YM30/PP‐g‐MA composites, which proved to be superior in tensile, flexion and impact strength and absorption of water compared to the untreated composite. The morphological analysis showed a better interaction between the fiber and the polymeric matrix for the composites with YM/APTS and YM/PP‐g‐MA, which corroborates the results of tensile and flexural strength, as well as with the spectra of FTIR in which the chemical modification of the fibers is observed. However, the results show that these treatments are promising in obtaining composites with recycled matrix with better properties. Abstract :